2006
DOI: 10.1093/aob/mcl153
|View full text |Cite
|
Sign up to set email alerts
|

stem fasciated, a Recessive Mutation in Sunflower (Helianthus annuus), Alters Plant Morphology and Auxin Level

Abstract: The observed phenotype and the high level of auxin detected in stf plants suggest that the STF gene is necessary for the proper initiation of primordia and for the establishment of a phyllotactic pattern through control of both SAM arrangement and hormonal homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 96 publications
(119 reference statements)
1
29
0
3
Order By: Relevance
“…Ray flowers were fixed as previously described (Fambrini et al 2006). Paraffin-embedded tissues were sectioned using a rotary microtome (Reichert, Vienna, Austria).…”
Section: Histological Analysismentioning
confidence: 99%
“…Ray flowers were fixed as previously described (Fambrini et al 2006). Paraffin-embedded tissues were sectioned using a rotary microtome (Reichert, Vienna, Austria).…”
Section: Histological Analysismentioning
confidence: 99%
“…The plant growth conditions used to cultivate the inbred line F11 and the WC mutant were reported by Fambrini et al [60]. Briefly, plants were grown in the field in replicate rows (50 cm interrow spacing with 25 -30 cm between plants; ca.…”
Section: Experimental Partmentioning
confidence: 99%
“…Changes in hormone metabolism also correlated with fasciation in hybrid Populus transformed with the Agrobacterium rhizogenes rolC gene, and fasciated tissues had a high level of free cytokinins (Nilsson et al 1996). It has also been shown that plants of Helianthus annuus with fasciated stems (STF) had higher endogenous free IAA levels (Fambrini et al 2006). The observed phenotype and the higher levels of auxin detected suggest that the STF gene is necessary for the proper initiation of primordia and for the establishment of a phyllotactic pattern through control of both shoot apical meristem arrangement and hormonal homeostasis (Fambrini et al 2006).…”
Section: Hormonal Content In Symptomless Versus Fasciated Tissuesmentioning
confidence: 94%
“…It has also been shown that plants of Helianthus annuus with fasciated stems (STF) had higher endogenous free IAA levels (Fambrini et al 2006). The observed phenotype and the higher levels of auxin detected suggest that the STF gene is necessary for the proper initiation of primordia and for the establishment of a phyllotactic pattern through control of both shoot apical meristem arrangement and hormonal homeostasis (Fambrini et al 2006). Furthermore, the increased hormonal levels point to a possible hormonal control mechanism of the development of fasciated shoot apical meristem phenotypes.…”
Section: Hormonal Content In Symptomless Versus Fasciated Tissuesmentioning
confidence: 99%